Pengembangan Ekonomi Kreatif Berbasis Kearifan Lokal Menuju Pariwisata Berkelanjutan di Kawasan Wisata Pantai Ujong Blang Lhokseumawe - Musrizal, Musrizal; Mukhlis, Mukhlis; Yusrawati, Yusrawari; Emi, Safrina (Aceh Journal of Community Engagement (AJCE), 2023)
This service activity aims to increase community empowerment in the creative economy sector based on local wisdom to achieve tourism in the Ujong Blang Lhokseumawe coastal area through understanding and ability to provide local creative economic products. This is certainly in line with the government's vision which continues to strive to encourage Indonesia both regionally and nationally to become a world tourist destination. The synergy of the creative economy and tourism becomes a magnet and enhances the enthusiasm of visitors to return and go to Ujong Blang beach as a tourist destination. Another aim of implementing this service is to foster synergy between universities and society, so that the existence of universities is not just for transferring knowledge formally but can also be done informally which has a positive impact on society. The material presented includes how to make a product marketing video, how to upload the video to YouTube and link it to various social media, and how to diversify local products in accordance with mutual agreement. The results of this service can be used as input for LPPM, lecturers and education staff to become material for teaching and research development and subsequent service